POCKET BOOK ON SELUANG FISH DIVERSITY AS ENRICHMENT MATERIAL FOR VERTEBRATE ZOOLOGY COURSE - Nida Hayati; Bunda Halang; Muhammad Zaini (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Rivers are the main habitat for fish groups, including Seluang fish of the genus Rasbora. Existence of these fish become a potential content for local potential-based biology teaching materials. Teaching materials with this content can be enriched. One form of supplementary teaching materials that can be developed based on local potential is a pocket book. This development uses Borg & Gall method. The results showed three types of fish, namely Rasbora argyrotaenia (Seluang Langkai), Rasbora tornieri (Seluang Kuning), and Rasbora dusonensis (Seluang Batang). Based on the pocket book validity test, it was declared very valid, with a value of 91.93%, dan the results of readability test by 6 students obtained 91.40%, pocket book has very good criteria.